2006
DOI: 10.1051/0004-6361:20052912
|View full text |Cite
|
Sign up to set email alerts
|

A continuous flaring- to normal-branch transition in Scorpius X-1

Abstract: We report the first resolved rapid transition from a Flaring Branch Oscillation to a Normal Branch Oscillation in the RXTE data of the Z source Sco X-1. The transition took place on a time scale of ∼100 s and was clearly associated to the Normal Branch-Flaring Branch vertex in the color-color diagram. We discuss the results in the context of possible association of the Normal Branch Oscillation with other oscillations known both in Neutron-Star and Black-Hole systems, concentrating on the similarities with the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 15 publications
(14 reference statements)
3
16
0
Order By: Relevance
“…1-2ks in the case of Sco X-1. 6 This is a known characteristic of NBOs in Sco X-1, and such a behaviour has been reported by, e.g., Casella et al 2006. an association between X-ray power spectra which combine NBO and HBO and the launch of the URF, and for an association between the hard apex and the corresponding flat-topped noise PDS and the launch of the lobes. We note, however, that the association between the launch of the URFs and the appearance of a NBO+HBO in the X-ray PDS is based on one single event for which both X-ray and radio data are available.…”
Section: Launch Of Urf #2mentioning
confidence: 67%
“…1-2ks in the case of Sco X-1. 6 This is a known characteristic of NBOs in Sco X-1, and such a behaviour has been reported by, e.g., Casella et al 2006. an association between X-ray power spectra which combine NBO and HBO and the launch of the URF, and for an association between the hard apex and the corresponding flat-topped noise PDS and the launch of the lobes. We note, however, that the association between the launch of the URFs and the appearance of a NBO+HBO in the X-ray PDS is based on one single event for which both X-ray and radio data are available.…”
Section: Launch Of Urf #2mentioning
confidence: 67%
“…Therefore, these three regions partially overlap, allowing type-B QPOs and type-A QPOs to ap-pear at different luminosity levels. This possibility is supported by the fact that while type-B QPOs are sometimes found in correspondence to peaks in the source flux for the case of GX 339-4 and Motta et al 2012 for GRO J16550-40), some other times it is type-A QPOs that are observed in correspondence to flux peaks (Casella et al 2004), similarly to what is seen for FBOs in NSs (Casella et al 2006).…”
Section: Nbos and Type-b Qposmentioning
confidence: 79%
“…arc length S along the track. However, in recent years authors have found several properties that do not A35, page 2 of 16 correlate (Wijnands et al 1996;Homan et al 2002;Casella et al 2006;Dieters & van der Klis 2000) so that S is not a measure ofṀ.…”
Section: A Monotonic Variation Of Mass Accretion Rate?mentioning
confidence: 99%